#TITLE_ALTERNATIVE# - PRASETYO (NIM 13605602), HENRY
Coconut fiber, hemp fiber, and coconut grain are abundant natural materials in Indonesia. However, until this very moment, those materials have not been used optimally. Although they have the advantage of being renewable compared to other synthetic fiber, such as glass fiber that can not be renewed. Therefore, making composite as an alternative of environmental friendly material, in the form of sandwich structure, starts to be taken into account. Nevertheless, sandwich structure, which is made of natural fiber as the basic material, still has a lot of weaknesses in the production process to material properties, which are still unknown specifically. One of the problems in sandwich structure in general is uniaxial force which can cause overall buckling. This final assignment gives details of the research conducted to identify the durability of natural based sandwich structure given uniaxial forces, which is shown by the value of critical buckling load (Pcr). Pcr can be obtained by doing experiments on a number of specimens which analyzed by southwell method and extrapolation. The experiment was begun by tension test for the face material which made from coconut fiber/epoxy which gave elastic modulus 0.5388 GPa and for hemp fiber/epoxy we can obtain E = 5.0844 GPa and while compression test was applied on the coconut fiber/latex for the core material, then we can obtain E = 0.017418 GPa. From the mentioned results, the hemp fiber/epoxy was chosen as the face material and the coconut grain/latex as the core material to build a sandwich structure. From the experiment result, we can obtain the varying value of the critical buckling load from the above three specimens that tested. The average critical buckling load that obtained was 35.03 N/mm for the southwell method and 32.45 N/mm for the extrapolation method. These results compared with the numerical result with varied delamination percentage were in range of 40% delamination.